Створення культури «бородатих» коренів рослин алтеї лікарської Althaea officinalis L. з використанням різних векторних конструкцій з геном ifn-α2b людини - Дробот, К.О.; Матвєєва, Н.А.; Кваско, О.Ю.; Шаховський, А.М. (Фактори експериментальної еволюції організмів, 2014)
Aim. The obtaining of marshmallow Althaea officinalis L. “hairy” root culture with human interferon α2b gene (ifn-α2b) was the aim of this work. Methods. We used Agrobacterium rhizogenes and different transformation vectors (pCB 124 and pCB 161) with ifn-α2b gene under constitutive 35S CaMV promoter or Mll rootspecific sugar beet promoter respectively. Also we used A. rhizogenes wild strain A4 for marshmallow genetic transformation. The genes were transferred into leafs, roots, stems and cotyledones explants via A. rhizogenes-mediated transformation. The presence of transgenes was determined by PCR analysis. Fructan content in “hairy” roots extracts was analyzed by Selivanoff-Probe. Results. Transformation frequency was up to 50 % if leaf explants was used for transformation (pCB124 vector or A. rhizogenes А4) and transformation frequency was up to 75 % for explants transformed using pCB161 vector. PCR analysis proved the presence of nptII, ifn-α2b and rolB genes in marshmallow roots obtained after A. rhizogenes-mediated transformation. The clones of transgenic roots differed in fructan synthesis. So the genetic transformation has led to increasing of the level of fructan content up to 41 mg/g dry weight. Fructan content was 13 mg/g dry weight in roots of control untransformed plants. Conclusions. Thus, we obtained the transgenic A. officinalis “hairy” roots using A.rhizogenes-mediated transformation. Extracts from “hairy” root culture were characterized by the higher level of fructan content in comparison with the fructan content in extracts from the roots of control plants.
Key words: genetic transformation, Agrobacterium rhizogenes, hairy root, Althaea officinalis L., fructans.